Shoulder Pain as The First Clue: A Case Report of Pancoast Tumor with Early Presentation - Munandar, Muhammad Akbar Ramadhan; Kusumastuti, Ira; Herlina, Liana; Munandar, Hendra Priatna (Respiratory Science, 2026)
Background: In some cases, shoulder pain can be an early sign of a serious condition, such as a Pancoast tumor. A Pancoast tumor is a type of lung cancer located in the upper lobe of the lung. These tumors are often difficult to diagnose because their symptoms are similar to those of musculoskeletal conditions. Case: A 68-year-old man presented with a three-month history of right shoulder pain. The pain had been treated with analgesics and acupuncture but showed no improvement. The patient reported experiencing shortness of breath over the past few days. The patient had a history of smoking and unintentional weight loss. A chest X-ray revealed atelectasis and a suspicious mass in the superior lobe of the right lung. A chest CT scan confirmed the presence of a mass in the superior lobe of the right lung. A biopsy was performed to confirm the diagnosis, which revealed poorly differentiated small cell carcinoma in the right lung. The patient was subsequently diagnosed with a Pancoast tumor (with staging T4N3M1a). Discussion: A pancoast tumor is a condition which oftenly overlooked due resemblane of musculoskeletal disorders. Shoulder pain caused by this tumor may result from the tumor invading surrounding tissues. It is important for physicians to perform a thorough evaluation of patients presenting with shoulder pain, especially when risk factors are present. Conclusion: Shoulder pain as an early symptom of a Pancoast tumor is an important clinical concern for healthcare professionals. Early detection through comprehensive and appropriate evaluation can significantly improve patient prognosis.